The Cities of Spanish America 1825-1914: Economic and Social Aspects - Halperín Donghi, Tulio (Urban History Review / Revue d'histoire urbaine, 1980)
The paper distinguishes three stages in the history of Spanish- American cities in this period. The first (1825-1850) is one of slow and uneven urban growth; it is also one of social readjustment to the new political and economic realities of independence, republic and comparatively free external trade. The urban upper classes are deeply fragmented in the process; the largely peninsular mercantile group is replaced by a much more isolated and smaller one, dominated by the British; the base of political power becomes less urban, and the city elites linked with Church and state suffer in their income and prestige; the progress of egalitarian ideas corrodes traditional deference. The lower groups are affected by the decadence of slavery and in the middle of urban society free trade brings about a crisis of many traditional crafts and the flowering of other artisanal and trade activities. The second stage (from 1850 to the seventies) continues, under a veneer of modernization in the urban lifestyle, the trends of the previous quarter-century. Urban growth quickens, but is again very uneven; the role of the state begins to gain in significance in comparison with that of an expanding trade. During the third stage large cities finally receive the full impact of the development of the new economies, based in the growth of exports and the gradual unification of the internal market: the completion of railway systems, from Mexico to Chile and Argentina, is of course a decisive factor in this change. Demographic growth and a new mode of social differentiation (which includes the creation of a larger dependent middle class and a modern working-class of wage earners in large enterprises, in transportation and services rather than in manufacture) bring about a change in residential patterns and the use of urban space. Even so, Spanish-American cities retain many elements from their past, and are usually quite far from the model of the growing capitals of continental Europe during the same years.